Antimicrobial Sensitivity Pattern of Microorganisms Isolated from Vaginal Infections at a Tertiary Hospital in Bangalore, India - Nagalakshmi Narayana-Swamy; Padmasri Ramalingappa; Urvashi Bhatara (University Library System, University of Pittsburgh, 2015)
Background: The vagina contains dozens of microbiological species in variable quantities and is, therefore, considered a complex environment. Among the microorganisms, bacteria have important repercussions on women's health. The present study was conducted especially to elucidate this type of vaginal isolates and their sensitivity towards currently used antibiotics. Methods: This was a retrospective study conducted at the Department of Obstetrics and Gynaecology, Sapthagiri Hospital, Bangalore, India from January 2012 to December 2013. All symptomatic women who had a high vaginal swab taken for culture and sensitivity testing were included in this study. Antibiotic susceptibility was tested using disc diffusion method (modified Kirby-Bauer method). The antibiotic sensitivity patterns of isolated microorganisms were studied. Results: Out of 200 patients, 95% had positive vaginal cultures. Fifteen types of microorganisms were isolated. The highest frequency of infection was observed at the age of 20-30 years, followed by 41-50 years and 31-40 years, and a low frequency of infection was observed above 50 years of age. The most prevalent pathogen was Escherichia coli, followed by Streptococcus agalactiae and diphtheroids with equal incidence. Among the antibiotics tested, isolated pathogens were completely resistant to nalidixic acid and highly sensitive to meropenem and imepenem. Conclusion: The high prevalence of gynaecological infections demands that patients with symptoms undergo thorough investigation with cultures and sensitivity essays. Changes in treatment protocols are required to treat vaginal infections effectively.